The Relationship Level of Knowledge of Teeth-Brushing to The Dental Caries Incidence in School-Age Children - Cahyaningrum, Febriana Dwi; Hermawati (Al-Hijrah Indonesia, 2023)
Background: The most common dental and oral diseases are dental caries and periodontal disease. The prevalence of dental caries in Indonesia is 88.8% with a root caries prevalence of 56.6%. Children aged 5-9 years have a prevalence rate of 92.6%. Purpose: To determine the relationship between the level of knowledge of brushing teeth and the incidence of dental caries in school-age children at Genengsari 01 Elementary School, Polokarto District. Method: This type of research is correlational (correlation) with a cross sectional approach. This study used a purposive sampling technique on school-age children or grades 1-3 as many as 48 respondents. Data analysis using somers`d test. The research instrument used a questionnaire and observation of dental examination. . Result: The results of this study showed that the level of knowledge was less and the number of dental caries was higher. Somers'd test results, p value 0.001 (<0.05), so it is proven that H0 from this study can be rejected, indicating a significant correlation was found between the level of knowledge of brushing teeth and the incidence of dental caries in school-age children in SD Negeri Genengsari 01 Polokarto District . The correlation coefficient value was obtained at 0.516, this means that there is a relationship between the two variables that is sufficiently correlated. Conclusion: There is a knowledge level of brushing relation to the incident of tooth caries in school-age children at Genengsari 01 Elementary School, Polokarkto District.